Effectiveness of Zanthoxylum piperitum-derived essential oil as an alternative repellent under laboratory and field applications - K. Kamsuk (2018)
Recently, there were considerable efforts made to promote the use of environmentally friendly and biodegradable natural insecticides and repellents, particularly from botanical sources. In this study, Zanthoxylum piperitum-derived essential oil isolated by steam distillation was investigated and compared to the standard synthetic repellent, N,N-diethyl-3-methylbenzamide (DEET), for repellency against mosquitoes under laboratory and field conditions. The oil of Z. piperitum alone and also with 5% vanillin added repelled laboratory-reared female Aedes aegypti with the median protection times of 1.5 and 2.5 h, respectively. These repellency times were proven to be significantly lower than those of DEET-based products: 25% DEET and 25% DEET + 5% vanillin demonstrating 3.5 and 5.5 h, respectively. However, when applied under field conditions, Z. piperitum oil + 5% vanillin was found to provide better protection against a wide range of natural mosquito populations than 25% DEET + 5% vanillin. While the product of DEET was effective in reducing bites with 99.7% protection, the protective effect of Z. piperitum oil product appeared complete (100%). It had a protective effect against Aedes gardnerii, Anopheles barbirostris, Armigeres subalbatus, Culex tritaeniorhynchus, Culex gelidus, Culex vishnui group, and Mansonia uniformis. The better repellency against a wide range of field mosquitoes derived from Z. piperitum oil products suggested an advantage of efficacy by providing a broad spectrum of activity. Therefore, Z. piperitum could have potential for use in the development of combined repellents as a natural active ingredient, synergist, or additive to conventional synthetic chemicals, particularly in situations when DEET is ineffective and impractical. © 2006 Springer-Verlag.